Influence of Internal Control Systems and Accounting Information Systems on Good Corporate Governance - Kamilia Lestari (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
This study aims to determine how the influence of internal control systems and accounting information systems on good corporate governance at Perum Bulog (Logistics Business Entity) in Bandung City. The factors tested in this study are the internal control system and the accounting information system as independent variables. Meanwhile, good corporate governance is the dependent variable. The research method used in this research is the verification method. The study population was employees of Perum Bulog (Logistics Business Entity Public Company) in Bandung, totaling 4,151 employees. The sampling technique used was probability sampling with simple random sampling method using the Slovin formula, so that there were 97 employees of Perum Bulog in Bandung City. The analytical method used is multiple linear regression analysis using SPSS Version 23.00. The results of the research partially and simultaneously show that the internal control system and accounting information system have an effect on good corporate governance at Bulog Corporation in Bandung City. In addition, the magnitude of the influence of the internal control system and accounting information system in contributing to good corporate governance is 77.2%.